Analisis Kompetensi Petani Pepaya California (Studi Kasus Kelompok Tani Merta Giri Kusuma Desa Abang, Kecamatan Abang, Kabupaten Karangasem) - SUDIARSANA, I GEDE ARTHA; DARMAWAN, DWI PUTRA; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Competence Analysis of California Papaya Farmers (A Case Study of Merta Giri Kusuma Farmer Group of Abang Village, Abang Sub-District of Karangasem Regency) The Ministry of Agriculture in the Strategic Plan 2015-2019 has a Gross Domestic Product target of 3.80% growth in the agricultural sector. Increased farm productivity is realized in the optimal utilization of land potential by applying the concept of agribusiness maximally. Efforts to increase productivity are conducted by increasing the competence of farmers namely knowledge, technical and managerial competence. The purpose of the study is to determine the level of competence of farmers, the level of productivity of California papaya farming, and the relationship between competence with productivity of California papaya farming. The research was conducted at Merta Giri Kusuma Farmer Group, Abang Village, Abang Sub-District, Karangasem Regency for 5 months. There are 20 members as population or the respondents taken by the census technique. Data analysis method used qualitative descriptive analysis and Rank Spearman correlation statistical analysis. In general, the competence of farmers is very significant ly related to the productivity of California papaya farming. A very real relationship at the 0.01 level is technical competence with a correlation coefficient of 0.835 and managerial competence with a correlation coefficient of 0,599. While the competence that is significantly related to the productivity of farming at the 0.05 level is the knowledge competence with the correlation coefficient of 0.465.